Apoyo familiar e inteligencia emocional en internas(os) de enfermería - Santillán Carrera, Lily Mariceli (2021)
The current study is quantitative type, descriptive correlational cross-sectional cut method, with the objective of determine the relationship between family support degree and emotional intelligence in nursing interns at the National University of Trujillo. The sample universe was made up of 66 interns who met the inclusion criteria. Two instruments were used for data collection: Leiton scale for family support degree (1997) and the Bar On ICE Emotional Inventory: NA - A - Unweighted (1997), adapted by Ugarriza (2001); the analysis of the relationship between variables was performed by using Kendall’s Tau B statiscal test. The results showed that 75.5 per cent of the interns presented a high family support degree, 22.7 per cent presented a moderate family support degree and 1.5 per cent a low family support degree. In addition, the findings showed that 65.2 per cent presented an average level of emotional intelligence, 33.3 per cent presented a high level and 1.5 per cent a low level. It was detected the existence of a significant statistical relationship between both variables (p=0.024).